THE EVALUATION Of PHYSICOCHEMICAL ANALYSIS OF PARAD SHODHAN - *Bachchhao Nikesh Dinkar; Suryawanshi Nilesh; Mehta Mahendra Tryambaklal; Tomar Ekta; Bhapkar Vedvati K (International Journal of Ayurveda and Pharma Research, 2015)
Rasa Shastra Dravyas includes minerals and metals which are mainly Bhumij in origin (obtained from earth), Parad (mercury) is also one among them. In Rasa Shastra, the extra ordinary importance of mercury is easily seen as the whole branch is named after Parad. In Rasa Shastra Parad cannot be adopted for therapeutic purposes without purification. Owing to their origin all the metallic and mineral drugs are likely to be associated with different varieties of impurities up to various degrees. Hence, they are advised to be processed with certain specific methods before their internal use. These methods are called Shodhan and they occupy a major portion of Rasa Shastra processing. These Shodhan procedures play a very important role in making metallic and mineral preparations free of toxicity and highly absorbable for quicker therapeutic effects even in minute doses. Parad is invariably a major constituent in most of the rasa preparations; it needs thorough purification and detoxification to render it fit for internal use. Rason is best among the Shodhandravya in Parad Samhita Paradshodhan with only Rason is mentioned..In this study Parad is triturated with Rasonkalka and then Kshalan is done. Parad loss in this study is very less amount. In ICP AES, Qualitative Analysis is done it reveals that following element in Parad before Shodhan Ag, Fe, Ga, Hg, Mg, Mn, Sr, Zn and after Shodhan Ag, B, Ca, Cr, Fe, Ga, Hg, Mg, Mn, Sr, Ti, Zn.